A Critical Evaluation and Comparison of Four Manufacturing Similation Softwares - Verma, Rajesh; Gupta, Ashu; Singh, Kawaljeet (Kathmandu University Journal of Science, Engineering and Technology, 2010)
An increase in the use of simulation as a modeling and analysis tool has resulted in a growing number of simulation software products in the market. Companies are seeking advice about the desirable features of software for manufacturing simulation, depending on the purpose of its use. Because of this, the importance of an adequate approach to simulation software evaluation and comparison is apparent. This paper presents a critical evaluation of several widely used manufacturing simulators: ProModel, AutoMod, HyperMesh and ProcessModel. Following a review of research into simulation software evaluation, an evaluation and comparison of the above simulators is performed. The main purpose of this evaluation and comparison is to discover the suitability of certain types of simulators for particular purposes. Keywords: Simulation; Simulation software; Evaluation; Comparison; Rating DOI: 10.3126/kuset.v5i1.2851 Kathmandu University Journal of Science, Engineering and Technology Vol.5, No.1, January 2009, pp 104-120